Correlation between serum cyclophilin A and acute ST-segment elevation myocardial infarction and its predictive value - Wang, Yuqi; Wang, Long; Fang, Caoyang; Chen, Zhenfei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveAcute ST-segment elevation myocardial infarction (STEMI) is a serious cardiovascular event, and timely diagnosis and intervention are essential to improve prognosis. As a novel biomarker, serum cyclophilin A (CyPA) may play an important role in the development and progression of STEMI.MethodsTwo hundred and sixty-four patients with acute STEMI and 264 healthy controls were included in this study. The association of CyPA with STEMI was assessed by multivariate logistic regression analysis, and the potential value of CyPA in predicting STEMI risk was assessed using receiver operating characteristic curve (ROC) and reclassification analysis. In addition, calibration curves and decision curve analysis (DCA) were used to test the reliability of CyPA in predicting STEMI risk.ResultsThe results showed that serum CyPA levels were significantly higher in patients with acute STEMI than in healthy controls (P < 0.001). Multivariate logistic regression analysis indicated that CyPA level was an independent risk factor for acute STEMI (OR = 1.15, 95% CI: 1.09, 1.23). In Model 3, each unit increase in CyPA was associated with a 17% increased risk of STEMI (P < 0.0001). Compared with Q1, the Q4 group (OR = 157.45, 95% CI: 65.19, 420.54) had a dramatically increased risk of STEMI. CyPA was found to have a non-linear relationship throughout the range by restricted cubic spline (RCS) analysis. The AUC of ROC curve analysis in model C was 0.994, which was significantly improved compared with model B (P = 0.01); the net reclassification index (NRI) was 0.0682 (P = 0.00029), and the comprehensive discriminant improvement index (IDI) was 0.0438 (P < 0.0001). The calibration curve showed that model C was more stable, and DCA showed that model C had better net yield, which was superior to model A and model B.ConclusionThis study showed that serum cyclophilin A levels were closely associated with the development of acute ST-segment elevation myocardial infarction. CyPA may become a potential biomarker for acute STEMI.